The Influence of Service Quality and Cafe Atmosphere on Customer Loyalty through Costumer Satisfaction as a Mediating Variable at Kopi Kenangan - Kautsar, Gandhy Muhamad; Juniwati; Hendri, M. Irfani; Heriyadi; Pebrianti, Wenny (Lentera Barasaki Publishing House, 2025)
This study aims to evaluate the influence of service quality and cafe atmosphere on customer loyalty, both direct and indirect through the mediating variable of customer satisfaction. The research employs a quantitative method with a purposive sampling approach, conducted on consumers of Kopi Kenangan in Pontianak City, West Kalimantan. The sample consists of 207 respondents. Data analysis was carried out using SmartPLS version 4 software with the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The results indicate that service quality and store atmosphere have a positive and significant effect on customer loyalty. Furthermore, customer satisfaction has been statistically proven to act as a mediating variable that strengthens the relationship between service quality and store atmosphere, influencing customer loyalty.